Customer Satisfaction towards Online Shopping in Kathmandu Valley - Niroula, Ballav; Gyanwali, Achyut (Patan Pragya, 2020)
Online consumer’s buying behavior consists of buying process of products and services through internet. Internet shopping is the process of buying goods and services from merchants who sell on the online. Online shopping allows buyers to buy sooner, more choices and can order products and services with comparative reasonable price. This study examines the factors affecting customer satisfaction towards online shopping in Kathmandu valley. The customer satisfaction is the dependent variable. Perceived service quality, perceived ease of use, perceived security and online payment process are the independent variables. The study is based on 408 respondents from the online shopping buyers of Kathmandu valley. Convenience sampling method was followed to select the respondents. To achieve the purpose of the study, structured questionnaire is prepared. Descriptive and explanatory research designs have been used. Correlation and regression analysis have been used to make analysis and draw the conclusion. The regression models are estimated to test the significance and importance of selected factors on customer satisfaction towards online shopping in Kathmandu valley. The result shows that there is positive relationship of perceived service quality and perceived ease of use with customer satisfaction. It is also found that online shopping has positive impact on customer’s satisfaction in Kathmandu valley. The findings of this study will be fruitful to researchers, policymakers, businesspeople and Government for academically as well as policy perspectives.